2021
DOI: 10.1016/j.tube.2020.102020
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of TB/COVID-19 Co-Infection: The phantom menace

Abstract: Despite the high number of victims of COVID-19, tuberculosis (TB) remains as the leading cause of death among infectious diseases worldwide. Since the beginning of the pandemic, there is an increasing number of studies trying to elucidate the interactions between Mycobacterium tuberculosis and SARS-CoV-2. The first case reports point to a worsening of respiratory symptoms in co-infected TB/COVID-19 individuals. However, data from the cohort studies has shown some conflicting results. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 71 publications
(55 reference statements)
0
68
0
12
Order By: Relevance
“…Our data on coinfected individuals suggests that LTBI is associated with elevated levels of CRP and α-2-M. Finally, LTBI is also associated with enhanced levels of two other biomarkers of disease pathogenesis in COVID-19 – VEGF and TGFα ( 28 ). Our study also reveals that cytokines for the most part (and chemokines, acute phase proteins and growth factors to a lesser extent) are significantly associated with LTBI positivity.…”
Section: Discussionmentioning
confidence: 61%
“…Our data on coinfected individuals suggests that LTBI is associated with elevated levels of CRP and α-2-M. Finally, LTBI is also associated with enhanced levels of two other biomarkers of disease pathogenesis in COVID-19 – VEGF and TGFα ( 28 ). Our study also reveals that cytokines for the most part (and chemokines, acute phase proteins and growth factors to a lesser extent) are significantly associated with LTBI positivity.…”
Section: Discussionmentioning
confidence: 61%
“…In this patient however, the sudden superinfection with COVID-19 resulted in a rapid worsening of respiratory function and, eventually, death. A recent review 2 suggested that tuberculosis and a previous history of tuberculosis seem to be related to an increased susceptibility to COVID-19, as well as worsening of the infection prognosis possibly because of a synergism between the two pathogens. This could explain the poor prognosis of our patient who, moreover, had already two important co-morbidities (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…1 The ongoing coronavirus disease 2019 (COVID-19) pandemic, which started in December 2019 in China, has overwhelmed healthcare systems globally and proved to be a new menace because of its devastating effect on lung function, especially in the more fragile patient. 2 This report describes the first case of miliary tuberculosis (TB) secondary to intravesical treatment with BCG with sudden worsening of respiratory function caused by COVID-19 superinfection.…”
Section: Introductionmentioning
confidence: 99%
“… 52 A synergy of these two infections could result in severe menacing consequences. 53 COVID-19 co-infection with TB has been reported to worsen the prognosis and increase morbidity and mortality in patients affected with this dual infection. 54 56 There is a sparsity of data regarding the number of patients who receive antitubercular as well as repurposed COVID-19 drugs simultaneously.…”
Section: Discussionmentioning
confidence: 99%